Recipient liver splitting to facilitate piggyback hepatectomy in adult living donor liver transplantation - Sung-Min Kim; Shin Hwang; Deok-Bog Moon; Dong-Hwan Jung (Korean Journal of Transplantation, 2021)
Recipient hepatectomy for an enlarged stony-hard liver is a demanding procedure, thus it is often accompanied by massive blood loss. Recipient liver splitting under prolonged hepatic inflow occlusion would facilitate the piggyback recipient hepatectomy. We herein present a case of recipient liver splitting, which was used for living donor liver transplantation (LDLT). A 48-year-old male patient diagnosed with acute-on-chronic liver failure underwent LDLT. During the recipient operation, the native liver was stony-hard and heavily adherent to the retrohepatic inferior vena cava (IVC). During liver mobilization, diffuse oozing occurred due to disseminated intravascular coagulation. As a change in the concept, we decided to perform in situ liver splitting of the recipient liver to facilitate dissection of the retrohepatic IVC. Under hepatic inflow occlusion, right-left liver splitting was performed along the usual plane of extended left hepatectomy. The procedures time for recipient liver splitting and removal was 60 minutes. A modified right liver graft recovered from his daughter was implanted according to the standard procedures of LDLT. We think that recipient liver splitting is a feasible technical option for coping with difficult recipient hepatectomy, especially in patients with an enlarged stony-hard liver and heavy adhesion around the IVC.